The Use of Social-Environmental Accounting Information by Managers of Non-Government-Organization to Support Decision Making - Wulan Dari; Nany Noor Kurniyati (Jurnal Mantik, 2022)
In order to achieve sustainability, organizations are starting to pay attention not only to financial issues, but also social and environmental issues. Then, recently, sustainability accounting or social-environmental accounting has emerged in order to convey information on financial, social and environmental responsibility for business sustainability. Various studies are still limited to the use of this information by external stakeholders (investors), this study uses internal parties, particularly managers, whether to consider social and environmental information in their decision making. In an attempt to fill the gap in social environmental accounting literature, this study explores the managers in nonprofit companies, particularly non-government-organization who claim to be social entrepreneurs. This research is bridged by stakeholder theory, with the hypothesis that internal parties (social entrepreneurship managers) consider social and environmental information in their decision making.